PHYSICAL-CHEMICAL AND COLLOID-MECHANICAL METHODS OF RESEARCH OF MODIFIED POLYMER REAGENTS OF THE M-PAA SERIES AND THEIR APPLICATION FOR OBTAINING OF OINTMENT - Dzhakipbekova N.O.,; Yeshchenko L.S.,; Isaeva A.N.,; Dzhakipbekov Е.О. ,; Issa A.B., (Academic Scientific Journal of Chemistry, 2019)
This article discusses the surface, bulk and structural properties of polymers. It was determined that the limit value σ for M-PAA (MEA) and M-PAA (PV) is established faster than for individual solutions. It has been established that in polymers viscosity and electrical conductivity increase with increasing concentration, i.e. M-PAA (MEA) and M-PAA (PV) are polyfunctional polyelectrolytes, polymers M-PAA (MEA) and M-PAA (PV) are thermostable. For the study a complex of physicochemical methods were used: potentiometry, spectroturbidimetry, conductometry, viscometry, IR spectroscopy, elemental analysis, thermogravimetry, measurement of surface tension by the Wilhelm method.